Analisis Nilai Moral dalam Novel “Dompet Ayah Sepatu Ibu” Karya J.S Khairen dan Implikasinya pada Pembelajaran Bahasa Indonesia - Mulyana, Asep; Samosir, Astuti; Rejeki, Suyekti Kinanthi (Jurnal Pendidikan Impola, 2025)
Literature serves not only as a source of entertainment but also as an effective medium for conveying moral messages to readers. The novel Dompet Ayah Sepatu Ibu by J.S. Khairen presents the story of characters struggling through life’s limitations, rich in humanitarian and spiritual values. This study aims to describe the moral values contained in the novel and examine their relevance to Indonesian language learning in schools. The approach used in this research is descriptive qualitative with content analysis as the primary method. Data were collected through in-depth reading of the novel, noting quotations that contain moral values, and categorizing them accordingly. The research instrument used was a moral value classification table that includes individual, social, and religious moral categories. The findings show that there are 100 instances of moral values in the novel, including optimism, responsibility, empathy, sacrifice, honesty, social care, prayer, gratitude, and faith. These values are reflected through the actions and dialogues of the main characters, as well as the settings and situations that represent social realities relevant to students' lives. The conclusion of this study states that the novel holds great potential as a literary resource in Indonesian language learning, particularly for instilling character values aligned with the principles of the Merdeka Curriculum